Exploring Teacher's Obstacles and Strategies Toward the Implementation of English as a Medium of Instruction in Homeschooling - Damayanti, Irma; Mukarto, F. X. (English Department FBS UNP, 2024)
The rapid pace of globalization has led to the widespread adoption of English as a Medium of Instruction (EMI) in Indonesia. Extensive attention has been devoted to examining academic challenges, yet the complexities associated with integrating English as a Medium of Instruction (EMI) into homeschooling settings have remained largely unexplored. This case study delves into the utilization of EMI for teaching Science and Math within a homeschooling context. Through meticulous observation and interviews, this investigation reveals that two primary obstacles emerge: the comprehension of Science and Math terminology in English and students' proficiency in the language. In their daily classes, students typically engage with Science and Math concepts using Indonesian, which presents a significant hurdle when encountering English terminology. EMI classes, offered as extracurricular activities, attracted participation from third- and fourth-grade students. To address the linguistic challenge, the teacher implemented a strategy of code-switching, adeptly recontextualizing unfamiliar vocabulary using everyday language. Recognizing the diverse language competency levels among students, collaborative learning and grouping strategies were employed to enhance effectiveness in addressing these challenges. This approach fostered an environment where students could support one another, facilitating improved understanding and engagement with the material.